Use of advanced strategies and data innovation in teaching English - Khasanova Farangiz (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The integration of media alongside traditional learning methods improves the quality of teaching and learning. Successful teaching establishes a link between a student's existing knowledge and the educational goals of the course. Incorporating media within the classroom sustains student engagement, reinforces understanding, cultivates enthusiasm for the subject, and elucidates the connectivity between various concepts.